The population structure and habitat use of resident of Mandarin Duck (Aix galericulata) in Wu River (Southwest China) - Canshi Hu (BMC Zoology)
Abstract Background The Mandarin Duck (Aix galericulata) has recently been recognized as a partial migrant in China. The resident population of this species is primarily recorded in southern China, which is not only the traditional wintering range, but also the southernmost breeding sites. However, little information is known about their abundance and habitat requirements during breeding periods. This study provided the first report on the structure of the resident population and the habitat used during the post-breeding period at a tributary of the Wu River in Guizhou Province, Southwest China, which was one of the recently identified breeding sites within the traditional wintering range. Results A total of 36 Mandarin ducks were recorded among 15 sites, and the mean population density was estimated to be 3.51 ± 3.06 ind./km. The observed adults sex ratio of males to females was 0.44:1. At the microhabitat scale, the results of logistic regression models indicated that the key habitat variables included the distance to the nearest forest edge (dist.forest), opening extent of valley (deg.valley) and distance to the nearest human settlement (dist.settlement). The Mandarin Duck preferred to use foraging sites near forest edges, where dense marginal growth of woodland and shrubs was present. Conclusion These findings suggested that dense vegetation along rivers could play a positive, important role in habitat use by the resident population of Mandarin ducks. Compared to traditional breeding ranges, both adults and ducklings of this species were more likely to experience human-related disturbances due to the limited availability of ancient trees outside villages. This information will contribute to provide baseline knowledge on the resident population of Mandarin ducks, and enhance understanding of the causes and consequences of breeding partial migration.